The genus Mycterothrips (Thysanoptera: Thripidae) in Iran, with three new species - Alavi, Jalil; Awal, Mehdi Modarres; Fekrat, Lida; Minaei, Kambiz (Zootaxa, 2013)
Three new species of Mycterothripsare described from Khorasan-e Shomali province in Northeast of Iran, M. mahvelatensis sp.n., M. nastarani sp.n. and M. sanubari sp.n.. An identification key is provided for both sexes of the nine species of Mycterothrips known from Iran. Host associations among these Iranian species, as well as the variation in number of pronotal posteromarginal setae, are discussed briefly.